Modelling, simulation and analysis of a single rectangular microstrip patch antenna characteristic - Thelaha, Bin Haji Masri. (Universiti Malaysia Sarawak, UNIMAS, 2001)
To investigated the microstrip patch antennas performance by studying and analyzing its characteristics and parameters that makes the microstrip elements resonates and radiates microwave signals into space.